Comparison of SOX-10, HMB-45, and Melan-A in Benign Melanocytic Lesions - Dass SE; Huizenga T; Farshchian M; Mehregan DR (Dove Medical Press, 2021)
Sabrina E Dass,1 Taryn Huizenga,2 Mehdi Farshchian,2 Darius R Mehregan2 1Wayne State University School of Medicine, Detroit, MI, USA; 2Department of Dermatology, Wayne State University, Detroit, MI, USACorrespondence: Mehdi FarshchianDepartment of Dermatology, Wayne State University, 18100 Oakwood Blvd., Suite 300, Detroit, MI, 48124, USAEmail mfarshch@med.wayne.eduPurpose: Different immunohistochemical stains are used in dermatopathology to stain melanocytes and diagnose benign and malignant melanocytic lesions.Methods: SOX-10, HMB-45, and Melan-A immunohistochemical stains were used to assess 32 biopsy specimens with a histologic diagnosis of lentigo. The total number of melanocytes stained with each immunohistochemical stain was counted and an average count was obtained from two readings.Results: Analysis of the data revealed a significant difference in staining melanocytes between these three immunostains (p=0.0010, ANOVA). SOX-10 stained 0.195 more melanocytes than HMB-45 (p=0.0026). Similarly, Melan-A stained 0.195 more melanocytes than HMB-45 (p=0.0011). However, the difference between SOX-10 and Melan-A was not statistically significant (p=0.9810).Conclusion: SOX-10 and Melan-A immunostaining stain more melanocytes than HMB-45. No significant difference was noted between Melan-A and SOX-10.Keywords: immunohistochemical stains, melanocytes, benign melanocytic lesion, lentigo, atypical junctional melanocytic hyperplasia